Cell penetration efficiency analysis of different atomic force microscopy nanoneedles into living cells - Penedo, Marcos; Shirokawa, Tetsuya; Alam, Mohammad Shahidul; Miyazawa, Keisuke; Ichikawa, Takehiko; Okano, Naoko; Furusho, Hirotoshi; Nakamura, Chikashi; Fukuma, Takeshi (Scientific reports, 2021)
Over the last decade, nanoneedle-based systems have demonstrated to be extremely useful in cell biology. They can be used as nanotools for drug delivery, biosensing or biomolecular recognition inside cells; or they can be employed to select and sort in parallel a large number of living cells. When using these nanoprobes, the most important requirement is to minimize the cell damage, reducing the forces and indentation lengths needed to penetrate the cell membrane. This is normally achieved by reducing the diameter of the nanoneedles. However, several studies have shown that nanoneedles with a flat tip display lower penetration forces and indentation lengths. In this work, we have tested different nanoneedle shapes and diameters to reduce the force and the indentation length needed to penetrate the cell membrane, demonstrating that ultra-thin and sharp nanoprobes can further reduce them, consequently minimizing the cell damage.